Typical Atrial Flutter in acute coronary syndrome with ST segment elevation: incidence, predictive factors and related mortality. - ZOUZOU, Hanane (Clinical Medicine And Health Research Journal, 2024)
Background: Typical Atrial Flutter in acute coronary syndrome with ST segment elevation is very rare and never reported as a separate electrocardiographic entity, but associated with atrial fibrillation. Its incidence isn’t reported in the literature, and no data about its predictive factors or related mortality, also its epidemiological data is lacking in Algeria. Aims: The main objective of our study is the determination of the frequency of typical atrial flutter in acute coronary syndrome with ST segment elevation, the secondary objective was the analysis of its predictive factors, and related mortality. Methods and materials: In this prospective study, conducted in the cardiology department of Hussein Dey hospital (Algiers-Algeria), 467 patients with acute coronary syndrome with elevated ST segment (87 women and 380 men) were enrolled between 28 February 2014 and 16 July 2015. The average age is 60 ± 13 years; at admission, a Holter recorder was attached for continuous ECG monitoring during 48 hours Kruskal’s ANNOVA or H tests were used for comparison of quantitative variables, χ2 test or Fisher’s exact test, were used for qualitative variables, all tests were performed with 1st species risk of 5%. Results: The frequency of typical atrial flutter is 0.4 % (2 patients), CI 95%: [0%-1%], multivariate analysis identified right heart failure as the only predictive factor. The risk of mortality expressed by Hazard Ration (HR) is 27 (CI95%: [3.5-207], p = 0.001); right heart failure is the only predictive factor of mortality identified in our study. Conclusion: typical atrial flutter is very rare in acute coronary syndrome with elevated ST segment, its predictive factor according to our study is right heart failure, and its occurrence increases the risk of hospital mortality.